Analysis of Students' Learning Difficulties in Solving Story Problems in Mathematics Learning for Class II of SD Negeri 091254 Batu Anam - Tinambunan, Cindy Clara; Purba, Natalina; Sitohang, Sukardo (Holistic Science, 2025)
This study aims to analyze the forms and factors of learning difficulties of second-grade students of SD Negeri 091254 Batu Anam in solving mathematical story problems. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation of five students with different achievement levels. The results showed that students experienced difficulties in understanding the context of the problem, converting information into mathematical form, and performing basic arithmetic operations such as addition and subtraction. Factors causing difficulties consisted of internal factors, namely low understanding of mathematical concepts, reading ability, and learning motivation, as well as external factors, such as lack of practice of story problems, monotonous learning methods, and minimal learning environment support. This study recommends the implementation of contextual, varied, and interactive learning strategies to improve students' understanding of mathematical story problems. These findings are expected to be a reference for teachers in designing more effective and meaningful learning for elementary school students.